Sense of Purpose Scale: Development and initial validation. Issue 3 (3rd July 2018) - Sharma, Gitima; Yukhymenko-Lescroart, Mariya; Kang, ZiYoung
ABSTRACT: This study focused on the development of the Sense of Purpose Scale and demonstrated three empirically interpretable subscales: awareness of purpose, awakening to purpose, and altruistic purpose. The results provided initial evidence for all three subscales reliability and validity with a sample of 300 undergraduate students. Future research should focus on the further validation and revision of items to increase all three subscales internal consistency.